The association of polymorphisms in 5-fluorouracil metabolism genes with outcome in adjuvant treatment of colorectal cancer. (September 2011) - Afzal, Shoaib; Gusella, Milena; Jensen, Søren Astrup; Vainer, Ben; Vogel, Ulla; Andersen, Jon Trærup; Brødbæk, Kasper; Petersen, Morten; Jimenez-Solem, Espen; Adleff, Vilmos; Budai, Barna; Hitre, Erika; et al.
Aim: The purpose of this study was to investigate whether specific combinations of polymorphisms in 5-fluorouracil (5-FU) metabolism-related genes were associated with outcome in 5-FU-based adjuvant treatment of colorectal cancer.Methods: We analyzed two cohorts of 302 and 290 patients, respectively, one cohort for exploratory analyses and another cohort for validating the exploratory analyses. A total of ten polymorphisms in genes involved in 5-FU pharmacodynamics and pharmacokinetics were studied. End points were disease-free survival (DFS) and overall survival. Multifactor dimensionality reduction was used to identify genetic interaction profiles associated with outcome.Results: Low-expression alleles in thymidylate synthase ( TYMS ) were associated with decreased DFS and overall survival (DFS:hazard ratio [HR] exploration 2.65 [1.40–4.65]; p = 0.004, HR validation 1.69 [1.03–2.66]; p = 0.03). A specific multifactor dimensionality reduction derived combination of dihydropyrimidine dehydrogenase and TYMS polymorphisms was associated with increased DFS (HR exploration 0.69 [0.49–0.98]; p = 0.04, HR validation 0.66 [0.45–0.95]; p = 0.03). Specific combinations of functional polymorphisms in DPYD and TYMS were demonstrated to be associated with DFS and overall survival in patients receiving adjuvant 5-FU-based treatment. Specifically high TYMS expression alleles seem to be associated with decreased DFS. Original submitted 13 April 2011; Revision submitted 10 June 2011